2008
DOI: 10.1021/jm701318x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks as Valuable Tools To Differentiate between Sesquiterpene Lactones’ Inhibitory Activity on Serotonin Release and on NF-κB

Abstract: Sesquiterpene lactones are the active components of a variety of medicinal plants from the Asteraceae family. They possess biological activities such as the inhibition of NF-kappaB and the release inhibition of the vasoactive serotonin. On the basis of a data set of 54 SLs, we report the development of a quantitative model for the prediction of serotonin release inhibition. Comparing this model with a previous investigation of the target NF-kappaB, structural features necessary for specific compounds could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The role of sesquiterpene lactones in the inhibition of the central transcription factor NF-κB is well documented [24]. Sesquiterpene lactones indicate the active principle of many of the anti-inflammatory drugs used in traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The role of sesquiterpene lactones in the inhibition of the central transcription factor NF-κB is well documented [24]. Sesquiterpene lactones indicate the active principle of many of the anti-inflammatory drugs used in traditional medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported on the essential oil composition of various Tanacetum species (El-Shazly et al, 2002;Goren et al, 2001;Greche et al, 2000;Judzentiene and Mockute, 2005;Kandemir et al, 2008;MajedJabari et al, 2002;Marongiu et al, 2009;Mockute and Judzentiene, 2004;Monfared et al, 2002;Piras et al, 2014;Polatoglu et al, 2011;Rohloff et al, 2004;Weyerstahl et al, 1999) and camphor, 1,8-cineole, ␣-thujone, carvone, thymol, trans-sabinyl acetate, borneol, caryophyllene oxide, (E)-myroxide, sabinene, bornyl acetate, isopulegone and artemisia ketone were identified as the major constituents. This genus is also found to contain sesquiterpene lactones (Aljancic et al, 2001;Mahmood et al, 2002), a large group of molecules with several biological activities (Chaturvedi, 2011;Ghantous et al, 2010;Kreuger et al, 2012;Lesiak et al, 2010;Merfort, 2011;Wagner et al, 2008;Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopentenones endowed with all‐carbon quaternary stereocenters represent an important class of privileged structural motifs that are often encountered in many prostaglandins, prostanoid derivatives, natural products, and other bioactive molecules, [ 1 ] as exemplified by (–)‐nigrosporione A, C and D, [ 2 ] helenalin, [ 3 ] ambrosin, [ 4 ] umbellulone [ 5 ] (Figure 1). Moreover, this skeleton could serve as a powerful intermediate to synthesize some natural products and pharmaceuticals [ 6‐8 ] due to the wide diversity of potential functionalizations at the enone unit.…”
Section: Background and Originality Contentmentioning
confidence: 99%